Contra-hate spin di media sosial twitter jelang pilpres 2019 dengan pendekatan strategi sun-tzu - Saukoly, Rizal Librek (Journal of National Paradigm-Based Resilience Strategy, 2024)
This study aims to identify hate spins through hate speech content on Twitter social media during the 2019 Presidential Election campaign, and analyze patterns of hate spin movements, strategies and obstacles to overcome hate spins using the Sun Tzu approach. Research methods with content analysis to analyze hate speech and hate spins that occur on Twitter ahead of the 2019 Presidential Election, starting 15 February-15 April 2019. There are 36 (thirty-six) hate spins that attack candidate pairs 01 and 12 (twelve) hate spin attacking candidate 02. There are four cyber-attack patterns in the form of hate spins, namely: a wave and gradual hate spin attacks on the same candidate pair, single hate spin attacks, and hate spin attacks attacking each other between the two teams of candidates. Polri uses several counter-strategies: (1) using a plan to win; (2) a strategy of dealing directly with the enemy; (3) a strategy of chaos; and (4) a strategy of losing. The obstacles faced are the competent police personnel were limited and the discretionary conditions of security and order. Policy recommendations require additional personnel both in quantity and quality for information and communication technology (ICT).